Farmer’s knowledge, attitude and practices on safety, quality and post harvest management of brinjal and tomato in some selected areas of Bangladesh - Khatun, M; Rahman, MS (Bangladesh Journal of Agricultural Research, 2020)
Abstract Not Available Bangladesh J. Agril. Res. 44(4): 695-702, December 2019